TaqMan-based quantification of invasive cells in the chick embryo metastasis assay - Htun van der Horst, Edward; Leupold, Jörg; Schubbert, Rainer; Ullrich, Axel; Allgayer, Heike (BioTechniques, 2004)
The chick embryonic metastasis (CEM) assay is a fast in vivo method to investigate the invasive properties of tumor cells. Until now, most quantification methods were semiquantitative and time-consuming. Here we describe a rapid quantification method using TaqMan® technology to quantify the invaded tumor cells in the chorioallantoic membrane of fertilized eggs. This method is based on specific detection of human ALU sequences. Moreover, it provides high sensitivity over a wide linearity range.
Elektronische Reproduktion der Druck-Ausgabe
Published online: 6 Jun 2018
Gesehen am 02.05.2022